Simultaneous Mapping of T1 and T2 Using Cardiac Magnetic Resonance Fingerprinting in a Cohort of Healthy Subjects at 1.5T. Issue 4 (28th March 2020) - Hamilton, Jesse I.; Pahwa, Shivani; Adedigba, Joseph; Frankel, Samuel; O'Connor, Gregory; Thomas, Rahul; Walker, Jonathan R.; Killinc, Ozden; Lo, Wei‐Ching; Batesole, Joshua; Margevicius, Seunghee; Griswold, Mark; et al.
Abstract : Background: Cardiac MR fingerprinting (cMRF) is a novel technique for simultaneous T1 and T2 mapping. Purpose: To compare T1 /T2 measurements, repeatability, and map quality between cMRF and standard mapping techniques in healthy subjects. Study Type: Prospective. Population: In all, 58 subjects (ages 18–60). Field Strength/Sequence: cMRF, modified Look–Locker inversion recovery (MOLLI), and T2 ‐prepared balanced steady‐state free precession (bSSFP) at 1.5T. Assessment: T1 /T2 values were measured in 16 myocardial segments at apical, medial, and basal slice positions. Test–retest and intrareader repeatability were assessed for the medial slice. cMRF and conventional mapping sequences were compared using ordinal and two alternative forced choice (2AFC) ratings. Statistical Tests: Paired t ‐tests, Bland–Altman analyses, intraclass correlation coefficient (ICC), linear regression, one‐way analysis of variance (ANOVA), and binomial tests. Results: Average T1 measurements were: basal 1007.4±96.5 msec (cMRF), 990.0±45.3 msec (MOLLI); medial 995.0±101.7 msec (cMRF), 995.6±59.7 msec (MOLLI); apical 1006.6±111.2 msec (cMRF); and 981.6±87.6 msec (MOLLI). Average T2 measurements were: basal 40.9±7.0 msec (cMRF), 46.1±3.5 msec (bSSFP); medial 41.0±6.4 msec (cMRF), 47.4±4.1 msec (bSSFP); apical 43.5±6.7 msec (cMRF), 48.0±4.0 msec (bSSFP). A statistically significant bias (cMRF T1 larger than MOLLI T1 ) was observed in basal (17.4 msec) and apical (25.0 msec) slices. For T2, a statistically significant bias (cMRF lower than bSSFP) was observed for basal (–5.2 msec), medial (–6.3 msec), and apical (–4.5 msec) slices. Precision was lower for cMRF—the average of the standard deviation measured within each slice was 102 msec for cMRF vs. 61 msec for MOLLI T1, and 6.4 msec for cMRF vs. 4.0 msec for bSSFP T2 . cMRF and conventional techniques had similar test–retest repeatability as quantified by ICC (0.87 cMRF vs. 0.84 MOLLI for T1 ; 0.85 cMRF vs. 0.85 bSSFP for T2 ). In the ordinal image quality comparison, cMRF maps scored higher than conventional sequences for both T1 (all five features) and T2 (four features). Data Conclusion: This work reports on myocardial T1 /T2 measurements in healthy subjects using cMRF and standard mapping sequences. cMRF had slightly lower precision, similar test–retest and intrareader repeatability, and higher scores for map quality. Evidence Level: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2020;52:1044–1052.